Suplementation of iron assosiated with increasing cholesterol levels in pregnant women - Mustika Pramestiyani; Gunarmi Gunarmi (Jurnal Kesehatan Ibu dan Anak, 2021)
Iron supplementation is the most broadly utilized way to deal with controlling the worldwide issue of iron lack paleness. This study aimed to prove the effect of iron supplementation on cholesterol levels of pregnant women. This study was experimental study which type was 3 groups with the post-test only design was employed to determine the cholesterol level in pregnant women. The sample was the pregnant women in Kepuharjo Village, Yogyakarta, Indonesia who intake iron supplements. It’s classified the intervention into 3 groups as no iron supplement use, iron supplement use ? 90 tablets and iron supplement use > 90 tablets. Each group included 30 pregnant women who fulfilled the inclusion and exclusion criteria.  Cholesterol level were presented with mean and standard deviation. ANOVA with LSD were performed to compare cholesterol level from all groups to the respective iron supplement group. The results revealed that cholesterol level among no iron supplement use, iron supplement use ? 90 tablets and iron supplement use > 90 tablets were 152.53 (SD 34.67), 175.53 (SD 34.67) and 239.50 (SD 41.27), respectively. There was a significant difference among the mean cholesterol level on three groups. The post-hoc test showed the group of iron supplement use less than equal to 90 tablets and the group of iron supplement use > 90 tablets differed statistically significantly in term of their cholesterol level. Optimum iron supplement dosage should be considered for pregnant women.